Prevalence of Lip Competency among Nepalese Adolescents with different Ethnic group of Kathmandu Valley - Yadav, Rajiv; Yadav, Neelam; Basel, Prem (Orthodontic Journal of Nepal, 2019)
Introduction: Esthetic is one of the outcome that is expected from orthodontic treatment. In orthodontic practice, lip protrusion has been observed with proclined upper and lower incisors in bimaxillary protrusion. Such lip protrusion has been shown to be reduced with backward movement of the anterior teeth, which often accompanies premolar extraction. Hence the aim of our study is to find out prevalence of lip competency among Nepalese Adolescents with different ethnic group of Kathmandu valley. Materials & Method: lt is a cross-sectional descriptive study. The study population included 14-18 year-old adolescents studying in high school of all three districts of Kathmandu Valley. An evaluation form was developed categorizing different levels of deep bite following WHO guidelines 1985 and accordingly data were recorded on it. Statistical Analysis: Data were analyzed with descriptive statistics using the Statistical Package for the Social Sciences (SPSS for Windows, Version 23) in which p-values were calculated by Pearson Chi-Square Tests. Result: Out of 935 screened students, 89.6% had competent lips and 10.4% had Incompetent lips. Female showed 91.9% of competent lips and 8.1% of incompetent lips. Male showed 87.8% of competent lips and 12.2% of incompetent lips. Among different ethnic group for lip competency, Advasi/Tharu showed 0.2%, Brahmin/chettri showed 61.6%, Dalit showed 0.6, janajati- Hi showed 35.8%, Madhesi showed 0.7%,Muslim showed 0.6% and others showed 0.3%. Among Brahmin/chettri 56.4% showed competent lips, 5.22% showed incompetent lips. However among Janajati-Hi 30.7% showed competent lips, 5.12% showed incompetent lips. Conclusion: The Prevalence of competent lips was 89.6% and incompetent lips was 10.4%. Among Genders both female and male showed higher percent of competent lips than incompetent lips. However competent lips were more associated with females. Among ethnic groups , Brahmin/chhetri have 61.6% of lip competency whereas Janajati-Hi have 35.8%. Rest of the ethnic group have less than 1% of lip competency. Among Brahmin/chettri 56.4% have competent lips, 5.22% have incompetent lips where as Janajati-Hi 30.7% have competent lips, 5.12% have incompetent lips.